2007
DOI: 10.1111/j.1442-2050.2007.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of p53, VEGF C, p21: could they be used in preoperative evaluation of lymph node metastasis of esophageal squamous cell carcinoma?

Abstract: The prognosis of esophageal squamous cell carcinoma is primarily determined by staging. Although radiological methods have revealed lymph node metastasis preoperatively, these radiological findings cannot be correlated with pathological staging. The aim of this study was to compare the expressions of p53, vascular endothelial growth factor C (VEGF C) and p21 with lymph node metastasis in preoperative endoscopic biopsy and postoperative resection material. Tissue samples were taken from 40 patients who had unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
(82 reference statements)
1
23
0
3
Order By: Relevance
“…Cell proliferation markers have been classified in three categories: [1] growth fraction markers; [2] markers of specific cell cycle phases; and [3] cell cycle time markers. Growth fraction that is the ratio of cells growing within the cycle can be easily identified by Ki-67 or MIB-1 antibodies, identifying antigen expression on phases G1, S, G2 and M of the cell cycle 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Cell proliferation markers have been classified in three categories: [1] growth fraction markers; [2] markers of specific cell cycle phases; and [3] cell cycle time markers. Growth fraction that is the ratio of cells growing within the cycle can be easily identified by Ki-67 or MIB-1 antibodies, identifying antigen expression on phases G1, S, G2 and M of the cell cycle 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several biological markers predicting lymph node metastasis of ESCC have been identified. For example, Han et al (23) demonstrated that p53 and vascular endothelial growth factor C (VEGF C) expressions were correlated with lymph node metastasis in patients with ESCC and suggested that immunohistochemical analysis of these molecules could be useful for determining preoperative lymph node metastasis. The present study demonstrated that the rate of lymph node metastasis in patients with p12 CDK2-AP1 negative-T1sm ESCC was significantly higher than that of patients with p12 CDK2-AP1 positive specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 gene is commonly mutated in human tumors (21,22); however, associations between mutant p53 expression and patient prognosis remain unclear. TP53 mutations often lead to a loss of tumor suppressor activity and an extended half-life; therefore, the accumulation of mutant p53 protein is detectable by immunohistochemistry (23). Previous studies have demonstrated that p53 expression correlates with tumor stage, lymph node metastasis and overall survival in EC (2,(23)(24).…”
Section: A B C Dmentioning
confidence: 99%
“…TP53 mutations often lead to a loss of tumor suppressor activity and an extended half-life; therefore, the accumulation of mutant p53 protein is detectable by immunohistochemistry (23). Previous studies have demonstrated that p53 expression correlates with tumor stage, lymph node metastasis and overall survival in EC (2,(23)(24). Consistent with these studies, p53 overexpression was found to be more frequent in lymph node-positive ESCCs in the current study.…”
Section: A B C Dmentioning
confidence: 99%